2013
DOI: 10.1016/j.ridd.2013.09.035
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a fundamental motor skill intervention in pre-schoolers with motor problems depends on gender but not environmental context

Abstract: This version is available at https://strathprints.strath.ac.uk/58118/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
2
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 50 publications
4
58
2
9
Order By: Relevance
“…Las habilidades motoras básicas, incluyendo las habilidades de movimiento corporal en el espacio y de manipulación y control de objetos, son las precursoras necesarias para poder desarrollar habilidades motoras más complejas, como puede ser la coordinación dinámica general (Bardid et al, 2013). En este estudio, los niños con retraso en su motricidad somática o motricidad manual mostraron un desarrollo psicomotor significativamente inferior.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Las habilidades motoras básicas, incluyendo las habilidades de movimiento corporal en el espacio y de manipulación y control de objetos, son las precursoras necesarias para poder desarrollar habilidades motoras más complejas, como puede ser la coordinación dinámica general (Bardid et al, 2013). En este estudio, los niños con retraso en su motricidad somática o motricidad manual mostraron un desarrollo psicomotor significativamente inferior.…”
Section: Discussionunclassified
“…La adquisición y desarrollo de las habilidades motoras fundamentales se produce durante los primeros seis años de vida del niño, momento a partir del cual las destrezas práxicas y motoras se perfeccionarán a través de la ejecución de las actividades de la vida diaria (Bardid, Deconinck, Descamps, et al, 2013 …”
Section: Introductionunclassified
See 1 more Smart Citation
“…Further, the follow-up study employed self-reported measures of physical activity and sedentary behavior, instead of actual measures of motor performance, which may have introduced an element of bias; individuals who were in the low-proficiency group originally may have misrepresented their actual activity levels. Interestingly, the study did find gender differences in physical-activity levels at the follow-up, with women from the higher-proficiency group, as measured at age 6, having less time spent in sedentary behaviors, which is consistent with other research in this area (Bardid et al, 2013, Colley et al, 2011a2011b;Thomas & French, 1985).…”
Section: Role Of Motor Competencysupporting
confidence: 88%
“…Recent research (Bardid et al, 2013;Stodden et al, 2014) suggests that the development of FMS at a young age is linked to physical activity levels later in life.…”
Section: Role Of Motor Competencymentioning
confidence: 99%